Aflatoxin B1 decontamination by UV-mutated live and immobilized Aspergillus niger. (March 2016) - Sun, Xiulan; Sun, Chao; Zhang, Xiaoxue; Zhang, Hongxia; Ji, Jian; Liu, Yuanfa; Tang, Lili
Abstract: The decontamination of Aflatoxin B1 (AFB1 ) by immobilized cells of a new mutant strain, prepared on a base of HSCAS (hydrated sodium calcium aluminosilicate), was studied. Novel strains were induced by UV irradiation, from which 50 were screened according to their degradation efficacy on AFB1, compared with the wild strain (FS-Z1). The FS-UV1 strain exhibited highest degradation efficacy, which was confirmed by 18SrDNA to be Aspergillus niger . The results indicate that both immobilized cells and this mutant strain which are incubated for 48 h at 30 °C, would considerably remediate AFB1 in nutrient broth culture, by 95.32% and 82.43%, respectively. By the application of samples of contaminated cottonseed meal, with results of 93.46%∼96.82%, the degradation rate was also validated. The results of Ames test indicate the mutagenic activity of treated AFB1 is greatly abated, with treated controls. The Application of LC-q-TOFMS (liquid-chromatography, quadrupole, time-of-flight mass spectrometry) deduces the structure and molecular formulas of the degradation products. In the vivo study, the damages of photomicrographic evidence are decreased in kidney and liver and the serum biochemical parameters is improved, in response to preventative treatment with immobilized cells. This is the application of HSCAS-prepared, immobilized A. niger cells to degrade AFB1 of contaminated samples. The investigation in this paper offers a novel path for economical, time-saving biodegradation of AFB1 in foods and feeds. Highlights: The mutant strains (FS-UV1) were obtained by UV irradiation and screened. Immobilized cells remediate AFB1 more effective than FS-Z1 strain. The Ames test and vivo study showed prophylactic efficacy.